2013
DOI: 10.1016/j.biomaterials.2013.02.065
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage functional polarization (M1/M2) in response to varying fiber and pore dimensions of electrospun scaffolds

Abstract: In this study, we investigated the effect of fiber and pore size of an electrospun scaffold on the polarization of mouse bone marrow-derived macrophages (BMMΦs) towards regenerative (M2) or inflammatory (M1) phenotypes. BMMΦs were seeded on Polydioxanone (PDO) scaffolds electrospun from varying polymer concentrations (60, 100, and 140 mg/ml). Higher polymer concentrations yielded larger diameter fibers with larger pore sizes and porosity. BMMΦ cultured on these scaffolds showed a correlation between increasing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
352
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 386 publications
(363 citation statements)
references
References 39 publications
11
352
0
Order By: Relevance
“…The immune response to tissue-engineered scaffold materials is critical to their success, and as such, investigators have explored whether physical factors, such as substrate topology, influence macrophage behavior. Interestingly, it has been observed that surface features indeed affect macrophage morphology and cytokine secretion profiles (31)(32)(33), as well as the overall and fibrotic responses (34), although the mechanisms underlying these responses have so far remained elusive. Our data suggest that topological cues might lead to different macrophage responses by influencing their shape and cytoskeleton.…”
Section: Discussionmentioning
confidence: 99%
“…The immune response to tissue-engineered scaffold materials is critical to their success, and as such, investigators have explored whether physical factors, such as substrate topology, influence macrophage behavior. Interestingly, it has been observed that surface features indeed affect macrophage morphology and cytokine secretion profiles (31)(32)(33), as well as the overall and fibrotic responses (34), although the mechanisms underlying these responses have so far remained elusive. Our data suggest that topological cues might lead to different macrophage responses by influencing their shape and cytoskeleton.…”
Section: Discussionmentioning
confidence: 99%
“…Although the cellular and molecular mechanisms of the biomaterial-host interaction are not entirely understood, it is well established that in addition to clearing debris and removing pathogens from the wound site, macrophages have been shown to be absolutely necessary for biomaterial degradation [157,158]. Macrophages produce a number of enzymes including matrix metalloproteinases (MMPs), collagenases, elastases and hyaluronidases that in addition to being important for ECM scaffold degradation, are also necessary for tissue reorganization [159][160][161]. ECM scaffold degradation is an important process that not only allows for the material to be physically replaced by newly synthesized tissue, but that also releases a wealth of cryptic molecules and growth factors contained within the scaffolds that facilitate and promote tissue remodeling and repair [56,60,76,77].…”
Section: Host Response To Implanted Ecm-derived Biomaterialsmentioning
confidence: 99%
“…MAC polarization can be effected by biomaterial fiber and pore size, where increased polymer concentrations lead to the presence of M2 MACs, which in turn lead to wound healing and regeneration [3]. It is also important to note that MACs are not permanently differentiated, but are plastic in that they possess the ability to switch back and forth between M1 and M2 depending upon the local environment [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…The charge on this chain is attracted to the grounded mandrel where it deposits randomly, creating a web of polymeric nanofibers. A previous study has shown that by varying the diameter of polydioxanone (PDO) electrospun scaffolds, the overall MAC behavior is affected [3]. When larger fiber diameters were used, MAC infiltration and the expression of the M2 phenotype increased.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation